2012
DOI: 10.2139/ssrn.2178997
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Asset Repurchases and Issues in an Experimental Market

Abstract: We create an experimental asset market in which we conduct share repurchases and share issues. Although the intrinsic value of the shares is independent of the quantity outstanding, the interventions result in changes in asset price. Specifically, we find the following.(1) A repurchase of shares increases the price of the asset, and a share issue decreases the price of the asset, compared to a benchmark of no intervention. These effects are consistent with downward-sloping demand for the asset. (2) The empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 50 publications
(31 reference statements)
3
29
0
Order By: Relevance
“…This approach has been followed in many studies e.g. Lei et al (2001); Noussair et al (2001); Dufwenberg et al (2005); Haruvy and Noussair (2006); Akiyama et al (2012); Haruvy et al (2013); Füllbrunn et al (2014).…”
mentioning
confidence: 99%
“…This approach has been followed in many studies e.g. Lei et al (2001); Noussair et al (2001); Dufwenberg et al (2005); Haruvy and Noussair (2006); Akiyama et al (2012); Haruvy et al (2013); Füllbrunn et al (2014).…”
mentioning
confidence: 99%
“…The rational speculator anticipates future price movements and purchases (sells) if she expects prices to rise (fall). Haruvy et al (2012) test whether this structure predicts the observed treatment differences in an experiment in which the experimenter purchases and resells units of asset. The model predicts a reshuffling among traders that induces a repurchase to exacerbate bubbles and a share issue of sufficient size to induce prices to track fundamentals.…”
Section: Traders' Emotional Statesmentioning
confidence: 99%
“…They do not find a correlation between emotional state and trading profits. Haruvy et al (2012) apply the model of DeLong et al (1990) to describe data from an asset market experiment with the structure of Smith et al (1988). The DeLong et al model postulates three trader types: fundamental value, momentum, and rationally speculating traders.…”
Section: Traders' Emotional Statesmentioning
confidence: 99%
“…The percentage of traders classified as each type is comparable in the four treatments. Haruvy and Noussair (2006) and Haruvy et al (2013) The market influence of traders of each type is shown in figure 3. It reveals that the NoSwap treatment is the only one characterized by having Fundamental Value traders with more market influence on average than the other two types over the entire session.…”
Section: Ivb Individual Behaviormentioning
confidence: 99%